2022
DOI: 10.1055/a-1761-5962
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of a New Method to Measure Cervical Proprioception

Abstract: Objective An accurate and reliable measurement of proprioception is important in the evaluation of the cervical. The aim of this study is to investigate the validity and reliability of a new method using Horizontal Plane Target Platform (HPTP) to assess Head Repositioning Accuracy (HRA) for Cervical Proprioception (CP). Methods HRA values of 86 healthy volunteers (21.01±2.16 yrs.) were measured through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In this study, we used the common assessment tools for dizziness, such as DHI, NDI, VAS, and posturography. There was a possibility to use an emerging tool to assess cervicogenic dizziness such as the Jenaer Standing Stability Score ( 25 ) or the Horizontal Plane Target Platform ( 26 ) in the future study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used the common assessment tools for dizziness, such as DHI, NDI, VAS, and posturography. There was a possibility to use an emerging tool to assess cervicogenic dizziness such as the Jenaer Standing Stability Score ( 25 ) or the Horizontal Plane Target Platform ( 26 ) in the future study.…”
Section: Discussionmentioning
confidence: 99%
“…CJPET measurements were performed with an AOS PropPoint® device with a laser apparatus. A validity and reliability study of the AOS PropPoint® device was performed by Köseo ğ lu et al [ 30 ], and according to the results obtained, it was found that the device is a valid and reliable method for the measurement of cervical proprioception. A 180° platform drawn with 1° intervals was used with the help of a small laser fixed to the head apparatus.…”
Section: Methodsmentioning
confidence: 99%